Effect of methanolic extract of piper sarmentosum leaves on neointimal foam cell infiltration in rabbits fed with high cholesterol diet - Amran, A.A.; Zakaria, Z.; Othman, Faizah; Das, S.; Al-Mekhlafi, Hesham Mahyoub; Raj, S.; Nordin, N. (2012)
Previous research has shown the beneficial effects of aqueous extract of Piper sarmentosum (P.s) on atherosclerosis. The first stage in atherosclerosis is the formation of foam cell. The aim of this study was to investigate the effect of the methanol extract of P.s on fatty streaks by calculating neointimal foam cell infiltration in rabbits fed with high cholesterol diet. Thirty six male New Zealand white rabbits were divided equally into six groups: (i) C: control group fed normal rabbit chow; (ii) CH: cholesterol diet (1 cholesterol); (iii) PM1: 1 cholesterol with methanol extract of P.s (62.5 mg/kg); (iv) PM2: 1 cholesterol with methanol extract of P.s (125 mg/kg); (v) PM3: 1 cholesterol with methanol extract of P.s (250 mg/kg); (vi) SMV group fed 1 cholesterol supplemented with Simvistatin drug (1.2 mg/kg). All animals were treated for 10 weeks. At the end of the treatment, the rabbits were fasted and sacrificed and the aortic tissues were collected for histological studies to measure the area of the neointimal foam cell infiltration using software. The thickening of intima ratio of atherosclerosis and morphological changes by scanning electron microscope were measured. The results showed that the atherosclerotic group had significantly bigger area of fatty streak compared to the control group. The area of fatty streak in the abdominal aorta was significantly reduced in the treatment groups which were similar with the SMV group. Similarly, there was a reduction in the number of foam cell in the treatment groups compared to the atherosclerotic group as seen under scanning microscope. In conclusion, histological study demonstrated that the methanol extract of the P.s could reduce the neointimal foam cell infiltration in the lumen of the aorta and the atherosclerotic lesion.